FINITE-ELEMENT MODELING OF ULTRA FINE PARTICLE FILTRATION BY A MEMBRANE-FILTER - SEO, YS; KIM, KU (WILEY-BLACKWELL, 1992)
Theoretical work has been carried out to investigate the filtration of ultra fine aerosol particles in a membrane filter. The analysis was done using a finite element method with a Newtonian fluid model for the carrier medium. Both inertial filtration and diffusional filtration were considered. Prior to the main analysis. our numerical scheme was tested with the analytical results for the diffusion of particles in the cylinder and showed good agreement, which confirms the importance of axial diffusion occurring in a short cylinder like a very thin membrane filter. Particle size, porosity, pressure drop. and flow velocity are found to be main variables that determine the filter efficiency. Two important mechanisms of filtration have opposite effects on the efficiency, depending on the variables. Increases in particle size, pressure drop, and flow velocity cause increases in the efficiency for inertial deposition, while decreases in those variables cause increases in the diffusional efficiency. The existence of a minimum value of total filtration efficiency (sum of inertial efficiency and diffusional efficiency) was indicated for intermediate values of the variables. Lower porosity is found to favor inertial deposition more than diffusion. Some other effects of filtration conditions on the total efficiency are also discussed.
Keywords: DIFFUSION; AEROSOLS